المسؤولية المخففة لعديم التمييز - علي أمجد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
Discrimination is the ability of a person to understand the nature of his act and its effects on him, and the lack of discrimination is the situation in which the person lacks that capacity. The general rule of tort in the Syrian Civil Code, as stated in 164, states that "Any mistake that causes harm to third parties is necessary for compensation." Therefore, the error of a person leads to the obligation to compensate for the damage caused by this error. It is obvious that the implementation of the text of the article requires a set of conditions and requires the availability of certain factors in each element of responsibility, namely error, damage and the causal relationship. One of the factors that should be available in the element of error, the cognitive factor, without realizing that there is no error from the ground, which led to the statement that the civil and criminal responsibilities of non-discrimination as a rule. However, the Syrian legislator noted some cases in which this provision avoids achieving justice, such as in the absence of an official responsible for non-discrimination or inability to obtain compensation from the official, which led the legislator to address these cases, The impact of mitigation. التمييز هو قدرة الإنسان على فهم طبيعة الفعل الذي يقوم به وآثاره عليه، وانعدام التمييز هو الحالة التي يكون فيها الشخص فاقداً لتلك القدرة(امامة اسماعيل،2012). وتنص القاعدة العامة للمسؤولية التقصيرية في القانون المدني السوري كما جاء في المادة 164 منه على أنه (كل خطأ سبب ضرراً للغير يلزم من ارتكبه بالتعويض) . وبالتالي فإن الخطأ الصادر عن شخص يؤدي إلى إلزامه بالتعويض عن الضرر الذي سببه هذا الخطأ. ومن البديهي أن إعمال نص المادة يتطلب توافر مجموعه من الشروط، كما يتطلب توافر عوامل معينه في كل عنصر من عناصر المسؤولية، وهي الخطأ والضرر وعلاقة السببية. ومن العوامل التي ينبغي توافرها في عنصر الخطأ، عامل الإدراك، فبدون إدراك لا يوجد خطأ من الأساس، وهذا ما أدى إلى القول بامتناع المسؤوليتين المدنية والجزائية عن عديم التمييز كقاعدة عامة. ولكن المشرع السوري لحظ بعض الحالات التي يبتعد فيها هذا النص عن تحقيق العدالة، كما في حالة عدم وجود مسؤول عن عديم التمييز، أو تعذر الحصول على تعويض من المسؤول، مما دعا المشرع إلى التوجه لمعالجة هذه الحالات، وهي الحالات التي يهدف هذا البحث لتحديدها وتحديد أثر تخفيف المسؤولية فيها .